PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEBSITE PADA SEKOLAH SMP SWASTA BUDI LUHUR DENGAN METODE WATERFALL - Niko Simahate; Nova Mayasari; Muhammad Zen (Jurnal Nasional Teknologi Komputer, 2026)
The library plays an important role in supporting teaching and learning activities in schools. However, library management at Budi Luhur Private Junior High School is still conducted manually, leading to inefficiencies in data processing, book searches, and borrowing transactions. This study aims to design and develop a website-based library information system to improve the effectiveness and efficiency of library management. The system was developed using the Waterfall method, which consists of requirement analysis, system design, implementation, testing, and maintenance. Data collection was carried out through observation, interviews, and documentation to identify system requirements. The system was implemented using PHP as the programming language and MySQL as the database. Black box testing was applied to evaluate system functionality based on input-output conformity. The results show that the developed system is capable of managing book data, member data, borrowing and returning transactions, and generating visitor and borrowing reports accurately and efficiently. Testing results indicate that all system functions operate as expected. The implementation of this system contributes to the digital transformation of school library management, improves service quality, and provides easier access to information for librarians and students. This research demonstrates that a website-based library information system developed using the Waterfall method can be an effective solution for modernizing school library services.